2012
DOI: 10.1093/glycob/cws092
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of 6-O-endosulfatase (Sulf-2) and its implications in synthesizing anticoagulant heparan sulfate

Abstract: Heparan sulfate (HS) 6-O-endosulfatase (Sulf) catalyzes the hydrolysis of 6-O-sulfo groups from HS polysaccharides. The resultant HS has reduced sulfation levels and displays altered biological activities. The Sulfs have been associated with several cancers and developmental problems and could function as a tool for editing specific HS structures. Here, we characterize the substrate specificity of human Sulf-2 using site-specifically radiolabeled synthetic polysaccharides. The enzyme was expressed and harveste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Enzymatic activity of the preparations was assessed using 4-MUS as a pseudosubstrate (25), and HS chains as a natural substrate followed by disaccharide analysis ( Supplemental Table S1). Results showed that HSulf-2 essentially targets [uronic acid-(2S)-N-sulfoglucosamine-(6S)] ([UA(2S)GlcNS(6S)]) trisulfated disaccharides, along with a small but significant decrease of the [⌬UA-GlcNS(6S)] disulfated disaccharide species, in agreement with previously published data (25)(26)(27)(28). To study in detail this desulfation mechanism without being hindered by the natural structural complexity of the intact polysaccharide, we analyzed HSulf-2 activity on a highly sulfated oligosaccharide that mimics heparin structure as well as the inner regions of HS S-domains.…”
Section: Analysis Of Hsulf-2 Enzymatic Activity On a Heparin Oligosacsupporting
confidence: 90%
“…Enzymatic activity of the preparations was assessed using 4-MUS as a pseudosubstrate (25), and HS chains as a natural substrate followed by disaccharide analysis ( Supplemental Table S1). Results showed that HSulf-2 essentially targets [uronic acid-(2S)-N-sulfoglucosamine-(6S)] ([UA(2S)GlcNS(6S)]) trisulfated disaccharides, along with a small but significant decrease of the [⌬UA-GlcNS(6S)] disulfated disaccharide species, in agreement with previously published data (25)(26)(27)(28). To study in detail this desulfation mechanism without being hindered by the natural structural complexity of the intact polysaccharide, we analyzed HSulf-2 activity on a highly sulfated oligosaccharide that mimics heparin structure as well as the inner regions of HS S-domains.…”
Section: Analysis Of Hsulf-2 Enzymatic Activity On a Heparin Oligosacsupporting
confidence: 90%
“…6-OST isoform 1 knockout is lethal to mice at the late embryonic stage, displaying systematic skeletal growth retardation, aberrant lung morphology, and reduced placental angiogenesis, whereas 6-OST isoform 2 knockout mice appear to be normal and fertile 20 . The cellular concentration of 6- O -sulfation is influenced by expression levels of 6-OST and endoglucosamine-6-sulfatases which selectively hydrolyze the 6- O -sulfo group present in the highly sulfated domains of HS containing the disaccharide repeating unit -IdoA2S-GlcNS6S- 21 .…”
mentioning
confidence: 99%
“…It is first well established that HS 6-O-sulfation is a major structural determinant for the interaction with many chemokines, including CXCL12 (78-80), CXCL8 (81,82), CXCL4 (83,84) and CCL5 (85). For the latter, the resolution of the CCL5 crystal structure in complex with heparin provided further evidence of the contribution of 6-O-S group in the interaction (85).…”
Section: Discussion: Potential Roles Of the Sulfs During Inflammationmentioning
confidence: 95%